Applying the Decision Rights to a Case of Hospital Institutional Design - Eid, Florence (World Bank, Washington, DC, 2014)
Corporatization, a hybrid between public sector ownership and privatization, is an organizational form that is increasingly being adopted in the social sectors. In the health sector, the high costs of public hospitals, new technological developments, changes in demand for primary and secondary health care, and efficiency considerations have necessitated shifts in organizational boundaries, leading to conversions in hospital ownership. In the past decade hospitals have been converted from public to nonprofit and from nonprofit to for-profit in industrial and developing countries alike. The debate around these conversions has centered mostly on the tradeoff between equity and efficiency involved in the shift from public to private provision of services. Eid argues that more important than this dichotomy is creating appropriate incentives and matching incentives with goals through institutional design. Because corporatization combines elements of both private and public ownership, it is difficult to design. Among the challenges is deciding where on the spectrum from a budgetary unit to a privatized enterprise a hospital should lie. Another challenge is aligning incentives-not just within the hospital but also between the hospital and the ministry of health. Eid draws on the decision rights approach to analyze how an innovative hospital in Lebanon, Hital Dahr El-Bachek (HDB), corporatized itself and became the best in the public sector over a period of seven years. To study HDB's experience, she develops a decision rights analysis framework that tracks the formation, evolution, and dilution of decision rights. She finds that: There are important lessons from bottom-up, demand-driven institutional design that can inform the design of top-down, supply-driven institutions, such as laws and regulations. An understanding of mechanisms of risk sharing and high-powered incentives created from the bottom up can inform the design of corporatized organizations. Key to good design are decision rights complementarities that provide the most complete (and flexible) contract possible, regardless of where ownership lies. In designing systemwide institutions for corporatization, Eid argues, risk transfer is important in satisfying the two most important objectives of the reform. The first objective is establishing hard budget constraints to control sectoral costs. At HDB, the decision right to raise revenue through user fees was complemented by decision rights that created accountability and legal liability. Together, these decision rights kept spending within HDB's means-in contrast with international experience with corporatization, where budget deficits have been a perennial problem. However, the informality of the decision rights precluded the exercising of those created to design long-term financial policy, resulting in timid capital expenditure plans. The second important objective of corporatization is improving hospital performance, including providing better service at a low cost for the patient. Eid argues that high-powered incentives are key. Among the most interesting of HDB's decision rights allocations was the pairing of claimant and control rights to produce high-powered incentives for the director. Not surprisingly, the most successful examples of corporatization worldwide have experimented with incentive schemes for hospital managers that seek to provide high-powered incentives in this way.